2022
DOI: 10.1002/ajum.12325
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of testicular atrophy based on sonographic findings immediately after successful manual detorsion

Abstract: Purpose To investigate and determine the sonographic findings obtained from manually distorted testes to predict testicular atrophy following manual detorsion. Materials and methods Twenty‐two patients who had been diagnosed with testicular torsion and undergone manual detorsion were included. These patients were classified according to the presence or absence of testicular atrophy. The duration of symptoms, presence or absence of hyperperfusion within the entire affected testis, and echogenicity (homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…Therefore, rapid detorsion is critical, and rapid diagnosis and treatment via manual or surgical detorsion play a crucial role in recovering testicular blood flow [ 7 9 ]. Unlike surgical detorsion, manual detorsion can be performed immediately after diagnosing testicular torsion, thereby decreasing the duration of testicular ischemia [ 7 , 10 16 ]. Reports on the use of point-of-care ultrasonography for the diagnosis of testicular torsion have increased in recent years [ 7 , 12 , 13 , 16 – 22 ]; however, no review article has described its use for manual detorsion and determined its success rates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, rapid detorsion is critical, and rapid diagnosis and treatment via manual or surgical detorsion play a crucial role in recovering testicular blood flow [ 7 9 ]. Unlike surgical detorsion, manual detorsion can be performed immediately after diagnosing testicular torsion, thereby decreasing the duration of testicular ischemia [ 7 , 10 16 ]. Reports on the use of point-of-care ultrasonography for the diagnosis of testicular torsion have increased in recent years [ 7 , 12 , 13 , 16 – 22 ]; however, no review article has described its use for manual detorsion and determined its success rates.…”
Section: Introductionmentioning
confidence: 99%
“…Torsion can result in obstruction of venous blood return, which can lead to enlargement of the testis and edema [ 20 , 24 , 28 30 ]. Testicular necrosis may also occur in some cases, with the affected testis exhibiting heterogeneous echogenicity [ 16 , 29 – 33 ]. Abnormal echogenicity can be detected by carefully comparing the echogenicity within the affected and unaffected testes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the simplest clinical research designs is a case series, such as presented by Hosokawa et al 4 who investigated the role of ultrasound in predicting a successful management of testicular torsion. They found that the presence of hyperperfusion in the affected testes after manual detorsion predicted a successful outcome (avoidance of testicular atrophy).…”
mentioning
confidence: 99%
“…One of the simplest clinical research designs is a case series, such as presented by Hosokawa et al 4 . who investigated the role of ultrasound in predicting a successful management of testicular torsion.…”
mentioning
confidence: 99%